Serialization Management for Best-Effort Hardware Transactional Memory - Gaudet, Matthew; Araújo, Guido; Amaral, José Nelson (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2015)
Most studies of Best-Effort HTM (BE-HTM) performance use a single serialization manager and a single parameter value across all benchmarks, inputs and thread counts. The experimental study in this paper indicates that the values chosen for serialization-manager parameters have a significant effect on performance in the Blue Gene/Q's (BG/Q) BE-HTM system. Moreover, for a given serialization manager, different benchmarks typically require different parameter values to achieve the best performance. BG/Q features two TM settings that represent two different HTM designs. A study of these two settings indicate that serialization-management decisions are also sensitive to changes in the HTM design. Therefore the choice of serialization management, including the tuning parameters, should be reevaluated for each new platform because effectiveness is affected even by relatively small changes to the HTM design.